Changes in the Composition of Atlantic Salmon upon the Brown Seaweed (Saccharina latissima) Treatment - Even Moen Kirkholt; Alexander Dikiy; Elena Shumilina (Foods, 2019)
This study shows the potential of improving the taste and shelf life of salmon by storing it in conjunction with sugar kelp. The influence of the addition of wet sugar kelp to Atlantic salmon fillet was assessed using a Nuclear Magnetic Resonance (NMR) metabolomics approach. Seaweed treatment caused significant changes in the polar and non-polar metabolic composition of salmon muscle upon its storage. The mutual diffusion of sugar kelp and salmon metabolites caused a significant decrease of the formation of the off-smelling compound trimethylamine and the biogenic amines, along with an increase of umami-related compounds (aspartate and succinic acid). Carotenoid composition of the seaweed-treated samples significantly differs from the reference samples. The amount of wet seaweeds used for the treatment and the time passed after the fish slaughter influence salmon quality parameters.